Sprinkler Irrigation System Planning for Horticulture Agriculture at Universitas Samudra Through Hydraulic Simulation and Operational Investment Cost Optimization - Wahyudi, Andri; A. Abdullah, Nasruddin; Amin, Muhammad; Amir, Fazri (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
The sprinkler irrigation system of horticultural agriculture at Universitas Samudra is able to increase the efficiency of water use when the climate change phenomenon hits. However, sprinkler irrigation requires quite high operational investment costs. The purpose of the planning is to obtain the design of the sprinkler irrigation network and optimize the operational investment costs of irrigation. The method used is hydraulic simulation of irrigation using variations in centrifugal and submersible transfer pump power and PVC pipe size. Furthermore, the results of the irrigation simulation were analyzed using the Taguchi method. The planning results show that the sprinkler irrigation network covers an area of 7,500 with an elevation of 6-8 meters above sea level. The water requirement for 53 sprinklers is 8.48 liters/second, and the total water requirement for horticultural plants is 2,063.2 per season. The use of a combination that can optimize the operational investment costs of irrigation is the use of centrifugal transfer pump power (0.6 kW), submersible transfer pump power (0.6 kW), and PVC pipe sizes of 1/2, 1, 1 1/2, and 2 inches. This combination produces an optimum water pressure prediction of 1.756 bars and produces an optimum electricity usage cost prediction per day of Rp. 30,350. By using centrifugal transfer pump power, submersible and low-capacity PVC pipe size makes it more cost-efficient compared to other combinations.